2007
DOI: 10.1007/s11240-007-9208-5
|View full text |Cite
|
Sign up to set email alerts
|

Micrografting of Protea cynaroides

Abstract: The inability to induce rooting of in vitro-established Protea cynaroides microshoots has prevented the production of complete plantlets. A successful shoot-tip micrografting technique was developed using in vitro-germinated P. cynaroides seedlings as rootstocks and axenic microshoots established from pot plants as microscions. Thirty-day old seedlings, germinated on growth-regulator-free, half-strength Murashige and Skoog medium, were decapitated and a vertical incision made from the top end. The bottom ends … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…the increased shoot length in the hypocotyls may be due to cambial contact and absence of competition from axillary buds that are present in the epicotyls. Although several authors have previously reported that in the micrografting of different plant species, e.g., cashew (34), pistachio (26), cherry (4) and King Protea (36), including almond (13), the size of the scion affects the success rate of micrografts, no significant difference in the frequency of successful micrografts was obtained in the three of the almond cultivars tested when the microscion was applied to different sizes. Fig.…”
Section: Acclimatizationmentioning
confidence: 97%
“…the increased shoot length in the hypocotyls may be due to cambial contact and absence of competition from axillary buds that are present in the epicotyls. Although several authors have previously reported that in the micrografting of different plant species, e.g., cashew (34), pistachio (26), cherry (4) and King Protea (36), including almond (13), the size of the scion affects the success rate of micrografts, no significant difference in the frequency of successful micrografts was obtained in the three of the almond cultivars tested when the microscion was applied to different sizes. Fig.…”
Section: Acclimatizationmentioning
confidence: 97%
“…However, use of cytokinin during shoot induction may carry over in shoots and subsequently suppress root formation. Shoot tip grafting has been used to produce virus-free plants (Navarro et al 1975), rejuvenate woody plants (Abousalim and Mantell 1992;Mneney and Mantell 2001), and was adapted for recovery of regenerated shoots of some species difficult to root, such as citrus (Peña et al 1995a, b), cotton (Luo and Gould 1999) and king protea (Wu et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, decapitated seedlings from surfacedisinfected seeds cultured in different media were used as rootstocks (Abousalim and Mantell 1992;Onay et al 2004;Suarez et al 2005;Raharjo and Litz 2005;Wu et al 2007). This system was proved to be excellent in facilitating grafting manipulations and in preventing root damage during micrografting.…”
Section: Resultsmentioning
confidence: 99%